The Association of Diabetes Mellitus with Premature Coronary Artery Disease: A Systematic Review of Pathophysiology, Biomarkers, and Clinical Outcomes - Caroline Johansyah; I Putu Oka Yudaswara Pande; Maria Johansyah (The International Journal of Medical Science and Health Research, 2025)
Introduction: Premature Coronary Artery Disease (PCAD), defined as atherosclerotic cardiovascular disease in young adults, represents a significant and escalating public health challenge with profound socioeconomic consequences. Diabetes Mellitus (DM) is recognized as a principal and potent risk factor for cardiovascular disease, yet the full spectrum of its association with the aggressive phenotype of PCAD requires a comprehensive synthesis of the available evidence. This systematic review aims to elucidate the multifaceted relationship between DM and PCAD, spanning from pathophysiology to clinical outcomes. Methods: This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search of PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library databases was performed to identify observational studies (cohort and case-control) examining the association between DM, prediabetes, or insulin resistance and PCAD. The methodological quality and risk of bias of included studies were rigorously assessed using the Newcastle-Ottawa Scale (NOS). A qualitative synthesis of the evidence was performed. Results: A total of 18 studies met the inclusion criteria. The evidence demonstrates a high prevalence of both diagnosed and previously undiagnosed DM in PCAD cohorts, often exceeding 30%. DM was significantly and consistently associated with increased angiographic severity, including a higher burden of multivessel disease and higher complexity scores. Clinically, DM emerged as a powerful independent predictor of adverse outcomes. Patients with PCAD and concomitant DM experience substantially higher rates of Major Adverse Cardiovascular Events (MACE), all-cause mortality, cardiovascular mortality, and recurrent myocardial infarction compared to their non-diabetic counterparts. Furthermore, novel biomarkers of insulin resistance, such as the Metabolic Score for Insulin Resistance (METS-IR) and the Triglyceride-Glucose (TyG) index, demonstrated superior predictive power for MACE over traditional metabolic markers. Discussion: The synthesized findings indicate that DM functions as a critical disease accelerator in the context of PCAD. The underlying pathophysiology, driven by insulin resistance and chronic hyperglycemia, fosters a systemic pro-inflammatory and pro-thrombotic state that promotes a more aggressive and diffuse atherosclerotic phenotype. The clinical implications are profound, highlighting a critical need for earlier risk stratification using novel biomarkers and more aggressive, multifactorial risk reduction strategies in young adults with metabolic dysfunction. Conclusion: The evidence robustly confirms that Diabetes Mellitus is a fundamental determinant of the risk, severity, and poor prognosis associated with Premature Coronary Artery Disease. This warrants a paradigm shift in clinical practice towards the early detection of insulin resistance and the implementation of intensive, secondary prevention-level care for young adults with DM to mitigate their substantial long-term cardiovascular risk.